Influence of Antibiotic Management on Microbial Selection and Infectious Complications After Trauma - Schindler, Cora Rebecca; Woschek, Mathias; Franz, Jan-Niklas; Störmann, Philipp; Henrich, Dirk; Marzi, Ingo (Frontiers in Medicine, 2021)
Background: The inflammatory response and post-traumatic complications like infections play an important role in the pathophysiology of severe injuries. This study examines the microbiological aspects in anti-infective treatment of trauma patients and their inflammatory response in post-traumatic infections complications. Patients and Methods: A retrospective analysis of prospectively collected data in trauma patients (ISS ≥ 16) over a 1-year period (01/2018 to 12/2018) is provided. Patient population was stratified into severely injured patients without post-traumatic infection (inf-PT), and severely injured patients who developed an infection (inf+PT). Results: Of 114 trauma patients, 45 suffered from post-traumatic infection during the first 10 days of hospitalization. Severely injured patients with concomitant traumatic brain injury (PT+TBI) showed the highest rate of post-traumatic infection. Pro-inflammatory reaction was tracked by levels of Interleukin (IL-)6 (day 3: inf+T 190.8 ± 359.4 pg/dL > inf-PT 56.2 ± 57.7 pg/mL (mean ± SD); p = 0.008) and C-Reactive-Protein (CRP, day 3: inf+PT 15.3 mg/dL > inf-PT 6.7 mg/dL, p = 0.001) which were significantly higher in trauma patients who develop an infectious complication and showed a significant positive correlation with the occurrence of infection. The leading entity of infection was pneumonia followed by infections of the urinary tract mainly caused by gram-negative Enterobacteriaceae. 67.5% of all trauma patients received single-shot antibiosis during initial care in trauma bay. The development of secondary colonization was not relevant positively correlated with single-shot antibiosis (r = 0.013, p = 0.895) and prophylactically calculated antibiotic administration (r = 0.066, p = 0.500). Conclusion: Severely injured trauma patients have an increased risk for development of infectious complications, which mainly is pneumonia followed by infection of the urinary tract mainly caused by gram-negative Enterobacteriaceae. Based on the data in this study, the one-time antibiotic and prophylactic calculated use of antibiotics, like Cephalosporins must be critically discussed in terms of their role in the development of post-traumatic infections and microbial selection.